Ethos, Opposition, and Identification Paul's Constitutive Rhetoric in 1 Thessalonians 1–3 - Glowasky, Michael (2023)
Because Paul's rhetoric in 1 Thessalonians is gentle and encouraging, especially when compared with his other letters, it has typically been taken as expressing his sincere thankfulness for the Thessalonian believers' faithfulness to the gospel in the face of opposition. This reading, however, overlooks the constitutive function of Paul's rhetoric, in which he does not merely describe the character the Thessalonian believers possess, but rather ascribes to them the identity he wishes them to embody. In this essay, I argue that, when considered from a constitutive perspective, Paul's ethos, his praise for the Thessalonians' faithfulness, and their shared opposition are rhetorically constructed for the purpose of fostering a sense of identification between himself and his readers and, thereby, to encourage them in their journey of faith.
Keywords: 1 Thessalonians; Kenneth Burke; Pauline rhetoric; Identification